Application of Video Based Learning Method to Increase Student Engagement in the Digital Age - Morisson, Buci; Sutisna, Uken; AnwarulUmam, Rayhan (Study Program of Madrasah Ibtidaiyah Teacher Education at Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2024)
The rapid development of digital technology has revolutionized the educational landscape, which demands more innovative and engaging teaching methods. One such method is Video-Based Learning (VBL), which utilizes multimedia resources, such as videos, to enhance students' learning experience. This article discusses the application of VBL as a strategy to enhance student engagement in the classroom in the context of the digital age. The research examines the effectiveness of VBL in encouraging active participation, enhancing understanding and strengthening students' motivation to learn. By integrating video content in the learning process, educators can provide a dynamic and interactive learning environment that suits various learning styles. In addition, VBL facilitates access to resources beyond traditional teaching, allowing students to interact with learning materials according to their pace and preferences. This research demonstrates the positive impact of VBL on student engagement, especially in subjects that benefit from visual and auditory stimulation, and discusses challenges and solutions in effective implementation. This article aims to provide insights and practical guidelines for educators in integrating Video-Based Learning in their teaching practices, so that students are better equipped to thrive in the digital age.